Deaf signers who know Japanese remember words and numbers more effectively than deaf signers who know English. - Flaherty M; Moran A (American Annals of the Deaf)
Deaf people have difficulty reading and remembering English script because of its sound-based orthography. Logographs (e.g., kanji, Arabic numerals) should not pose the same challenge because they are based on meaning, not sound. Little research has been conducted to test this theory's validity cross-culturally. The present study was an attempt to do just that. The first of two experiments tested immediate memory spans for word sequences of 20 hearing Irish, 20 prelingually deaf Americans, 20 hearing Japanese, and 20 prelingually deaf Japanese. For English words, deaf participants showed shorter memory spans than hearing participants, but memory spans were similar for deaf and hearing participants for words in kanji, the logographic system for Japanese writing. The second experiment tested memory span for Arabic numerals, with the same participants. Deaf English-readers showed shorter memory spans than their hearing counterparts, but deaf and hearing Japanese performed similarly.